Effect of pulsed electromagnetic field on in vitro and in vivo neural differentiation, cell survival of human mesenchymal stem cells - U, Enerelt; M, Tsogbadrakh; P, Jung-Keug (Scientific transaction of the National University of Mongolia. Physics, 2022)
Low frequency-pulsed electromagnetic fields (LF-PEMFs) affect many biological processes such as differentiation, regulation of transcription factor and cell proliferation. However, the fundamental mechanisms responsible for these effects remain unclear. The aim of this study is to understand the mechanisms underlying PEMF-mediated suppression of apoptosis and promotion of survival, including PEMF-induced neuronal differentiation on in vivo and in vitro. Treatment of induced human BM-MSCs with PEMF increased the expression of neural markers such as NF-L, NeuroD1 and Tau. Moreover, treatment of induced human BMMSCs with PEMF greatly decreased cell death in a dose- and time-dependent manner. There is evidence that Akt and Ras are involved in neuronal survival and protection. Activation of Akt and Ras results in the regulation of survival proteins such as Bad and Bcl-xL. Thus, the Akt/Ras signaling pathway may be a desirable target for enhancing cell survival and treatment of neurological disease. C57B6 mice were exposed to LF-PEMF (F = 60Hz, Bm = 10mT) after photothrombotic occlusion. We measured the BDNF/TrkB/Akt signaling pathway, pro-apoptotic and pro-survival protein and gene expressions, and the expression of inflammatory mediators and performed behavioral tests in both LF-PEMF-treated and untreated ischemic stroke mice. Our analyses showed that PEMF exposure dramatically increased the activity of Akt, Rsk, Creb, Erk, Bcl-xL and Bad via phosphorylation. PEMFdependent cell protection was reversed by pretreatment with LY294002, a specific inhibitor of phosphatidylinositol 3-kinase (PI3K). Our data suggest that the PI3K/Akt/Bad signaling pathway may be a possible mechanism for the cell-protective effects of PEMF. Also results indicated that LF-PEMF treatment promotes activation of the BDNF/TrkB/Akt signaling pathway. Subsequently, pro-survival proteins were significantly increased, while proapoptotic proteins and inflammatory mediators were decreased in ischemic stroke mice after LF-PEMF treatment. The results demonstrated that LF-PEMF exposure has a neuroprotective effect after ischemic stroke in mice during the recovery process.